2012
DOI: 10.1117/12.906430
|View full text |Cite
|
Sign up to set email alerts
|

Confocal microlaparoscope for imaging the fallopian tube

Abstract: Recent evidence suggests that ovarian cancer can originate in the fallopian tube. Unlike many other cancers, poor access to the ovary and fallopian tubes has limited the ability to study the progression of this deadly disease and to diagnosis it during the early stage when it is most amenable to therapy. A rigid confocal microlaparoscope system designed to image the epithelial surface of the ovary in vivo was previously reported. A new confocal microlaparoscope with an articulating distal tip has been develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Images obtained by these probes in real time during surgery have shown a clear distinction between normal and abnormal regions within the ovarian surface epithelium [45]. Studies using a flexible microlaparoscope have demonstrated the ability to provide high-resolution images of early-stage carcinoma inside the fallopian tube in the intraoperative setting [46]. Unfortunately, image quality produced by the microlaparoscope is diminished when compared to traditional laparoscopes due to a smaller scope size, focal distance, and a reduced light output.…”
Section: Confocal and Flexible Microlaparoscopymentioning
confidence: 99%
“…Images obtained by these probes in real time during surgery have shown a clear distinction between normal and abnormal regions within the ovarian surface epithelium [45]. Studies using a flexible microlaparoscope have demonstrated the ability to provide high-resolution images of early-stage carcinoma inside the fallopian tube in the intraoperative setting [46]. Unfortunately, image quality produced by the microlaparoscope is diminished when compared to traditional laparoscopes due to a smaller scope size, focal distance, and a reduced light output.…”
Section: Confocal and Flexible Microlaparoscopymentioning
confidence: 99%
“…Images obtained by these probes in real-time during surgery have shown a clear distinction between normal and abnormal regions within the ovarian surface epithelium ( 33 ). Furthermore, studies using a flexible microlaparoscope have demonstrated the ability to provide high-resolution images of early stage cancer inside the fallopian tube in the intra-operative setting, thereby facilitating both an earlier diagnosis and accurate disease staging ( 34 ). Since these procedures have shown merit in surgical settings, they may become a viable complementary option to traditional biopsies as future modalities of disease confirmation ( 33 ).…”
Section: Development Of Imaging Technologies Aimed At Early Detectionmentioning
confidence: 99%